The Teaching of Writing in EFL Classes - Srikandi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
Writing plays important roles in the context of English teaching as a foreign language in Indonesia. Writing is a communicative way of sharing observation, information, thoughts, or ideas with ourselves and others. Through writing, the language learners learn to communicate with other people, to understand them, to read what they have written, and to write to them. Writing as one of the language skills is not acquired naturally. Writing is considered the most difficult and complicated language skill to be learned compared to other language skills. Learning to write fluently and expressively is the most difficult of four language skills for all students. In the teaching of writing, the English teacher should pay attention on some elements, they are: (1) understanding the purposes of teaching writing, (2) teaching five main stages in producing a writing; pre-writing, drafting, revising, editing and publishing, (3) teaching how to develop a paragraph which consists of three major structural parts: a topic sentence, supporting sentences, and concluding sentence, (4) employing appropriate techniques, such as brainstorming, quetioning, and clustering in their teaching, and (5) introducing some text type to the students, such as: narration, description, procedure, news item, report, recount, anecdote, hortatory exposition, analytical exposition, commentary, discussion, and explanation.